1970
DOI: 10.1139/y70-090
|View full text |Cite
|
Sign up to set email alerts
|

Changes in specific airway resistance during prolonged breathing of moist air

Abstract: Effects of increased water content of inspired air at 21–38 °C on specific airway resistance (sRaw) in 107 healthy subjects were measured with a body plethysmograph. Mean sRaw increased insignificantly at 23 °C with 92% relative humidity (water content, 20.7 g∙m−3) for up to 71 h but became significant at 6 h with water content 25 g∙m−3. Increases were greater when evaporated tap water was inhaled than when distilled water was used. It is postulated that the increase in sRaw is due to mucosal swelling and to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

1971
1971
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Expiration always results in some loss of heat and moisture to the external air (Cole, ). In cold environments, where retention of body heat is a thermoregulatory imperative (Holliday, ; Ruff, ), mucosal recuperation of heat and moisture during expiration not only facilitates preparation for the next bout of inspiratory air modification (Walker et al, ; Yokley, ) but also reduces the total amount of body heat lost to the external environment (Cole, ; Melville, Josenhans, & Ulmer, ). Hot‐dry : requiring minimal warming but substantial humidification of inspired air, as well as considerable recuperation of moisture during expiration. Recovery of moisture during expiration will also result in the transfer of latent heat to the mucosa (Cole, ; Walker et al, ), but pressure to eliminate heat during expiration is likely mitigated by the superiority of sweating as a thermoregulatory cooling mechanism in hot environments with low relative humidities (Frye & Kamon, ; Lieberman, ; Ruff, ). Hot‐wet : requiring only minimal warming and/or humidification during inspiration but maximal elimination of heat during expiration.…”
Section: Discussionmentioning
confidence: 99%
“…Expiration always results in some loss of heat and moisture to the external air (Cole, ). In cold environments, where retention of body heat is a thermoregulatory imperative (Holliday, ; Ruff, ), mucosal recuperation of heat and moisture during expiration not only facilitates preparation for the next bout of inspiratory air modification (Walker et al, ; Yokley, ) but also reduces the total amount of body heat lost to the external environment (Cole, ; Melville, Josenhans, & Ulmer, ). Hot‐dry : requiring minimal warming but substantial humidification of inspired air, as well as considerable recuperation of moisture during expiration. Recovery of moisture during expiration will also result in the transfer of latent heat to the mucosa (Cole, ; Walker et al, ), but pressure to eliminate heat during expiration is likely mitigated by the superiority of sweating as a thermoregulatory cooling mechanism in hot environments with low relative humidities (Frye & Kamon, ; Lieberman, ; Ruff, ). Hot‐wet : requiring only minimal warming and/or humidification during inspiration but maximal elimination of heat during expiration.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the makeup and consistency of the mucus lining layer, i.e. changes in pH may produce a neural effect causing bronchoconstriction [Melville et al, 1970], Coupled with this is the fact that tap water has a higher concentration of dissolved contaminants which can cause in creases in sRaw and could possibly explain the greater percentage in crease in sRaw seen with tap water in this study. Experiments to eluci date the exact mechanism of increased sRaw with increased water con tent (separate communication) revealed that the increase is most likely due to bronchospasm and mucosal swelling since it was partly reversed by epinephrine and completely reversed by atropine.…”
Section: Discussionmentioning
confidence: 72%
“…Recent stud ies have shown that increased humidification of inspired air increases airway resistance in healthy individuals [Melville et al, 1970], in pa tients with respiratory diseases [M elville and W ard, 1971; C heney and B utler, 1968; and produce gross pathological changes in the lungs of dogs [M odell, 1968], Ambient air (22 °C, 50% relative humidity, 9.71 g/m3 water content) is assumed to be saturated and at body temperature by the time it reaches the tracheal bifurcation, so that any saturation deficit must exist in the small segment between nasal orifice and bronchi [M elville et al, 1970]. Increasing the water content of inspired air should not theoretically affect airway resistance unless the air is incompletely saturated at the tracheal bifurcation as as-' Technical assistance by Sheila McGann and N. Glasgow.…”
mentioning
confidence: 99%
“…An increase in depth of the airway lining's aqueous layer may make it impossible for the cilia to reach the mucous layer and thus impair mucus transport. Furthermore, if the aerosol deposition rate exceeds absorption capacity, this may lead to increased airway resistance [61,62] and possibly narrowing or occlusion of small airways. Severe systemic overhydration subsequent to ultrasonic aerosol therapy has been described in a term newborn infant [63], and similar occurrences have been reported in adults [64].…”
Section: Aerosol Applicationmentioning
confidence: 99%